DISTRIBUTION OF PHYTOPLANKTON IN THE ARABIAN SEA BETWEEN CAPE COMORIN AND COCHIN - Chennubhotla, V S K (Indian Journal of Fisheries, 2011)
The phytoplankton samples collected from the continental shelf and offshorewaters of the region between Cape Comorin and Cochin during the cruises of R. V. Varunain 1964-65 were studied by displacement volume and dryweight methods, and thevalues were represented by isolines to find out the relative abundance of the phytoplanktonin the different regions in the different months. Phytoplankton was foundto be abundant in the months of May and June in the areas between 8°—10° N and75°—77° E in terms of displacement volume and dry weight. The estimated values forthis region are higher than those values obtained for areas like the English Channeland Gulf of Maine at the height of bloom there.